Higher Molecular Weight Polyethylene Glycol Increases Cell Proliferation While Improving Barrier Function in an In Vitro Colon Cancer Model. (1st October 2011) - Bharadwaj, Shruthi; Vishnubhotla, Ramana; Shan, Sun; Chauhan, Chinmay; Cho, Michael; Glover, Sarah C.
Abstract : Polyethylene glycol (PEG) has been previously shown to protect against enteric pathogens and prevent colon cancer invasion. To determine if PEG could indeed protect against previously observed pro-invasive effects of commensal E. coli and EPEC, Caco-2 cells grown in an in vitro model of colon cancer were infected with strains of human commensal E. coli or EPEC and treated with 10% PEG 3350, PEG 8000, and PEG 20, 000, respectively. At 24 hours after infection, MMP-1 and MMP-13 activities, cell cluster thickness, depth of invasion, and proliferation were determined using standard molecular biology techniques and advanced imaging. We found that higher molecular weight PEG, especially PEG 8000 and 20, 000, regardless of bacterial infection, increased proliferation and depth of invasion although a decrease in cellular density and MMP-1 activity was also noted. Maximum proliferation and depth of invasion of Caco-2 cells was observed in scaffolds treated with a combination of commensal E. coli strain, HS4 and PEG 8000. In conclusion, we found that PEG 8000 increased cell proliferation and led to the preservation of cell density in cells treated with commensal bacteria. This is important, because the preservation of a proliferative response in colon cancer results in a more chemo-responsive tumor.